0663 Buprenorphine/naloxone Treatment Of Refractory RLS. (12th April 2019) - Forbes, Alison; Saini, Prabhjyot; Rye, David B
Abstract: Introduction: Schedule II opioids are often the final medication class prescribed for refractory RLS, but use is limited by concerns over tolerance, dependence, respiratory depression, prescription monitoring and dispensing. Buprenorphine (B) is a Schedule III partial mu-opioid receptor agonist, with a 24-48 hr half-life, often formulated with the antagonist naloxone (N) to manage opioid dependence. We report our open label experience with B/N. Methods: Seven subjects (5 men) were prescribed B/N. Average age was 68 ± 2.5 (SD), BMI 31.3 (± 7.7), and RLS disease duration 30.7 ± 18.9 yrs. Over their 10.7 ± 7.5 yr treatment courses, 9.3 ± 1.1 medications (2.4 ± 0.5 of which were opioids) had been tried, and 3 had received iv iron. Dopamine agonist therapy was limited by augmentation (N=6) and impulse control disorders (N=3). OSA was mild (N=2), moderate (N=2), or severe (N=3). Mobilizable iron stores were normal in six. Results: Treatment inadequacy contributed to loss of employment (N=2), diminished work productivity (N=3), CPAP non-adherence (N=3 of 4), and MVAs (N=2). Opioid therapy was limited by insomnia (N=2), sleepiness (N=2), anxiety (N=2), pruritis (N=1), lack of efficacy (N=1), or waning in dose duration benefit (N=3) manifesting as "withdrawal myoclonus"/waking periodic leg movements (PLM) (N=2). After discontinuing opioids, 2.0/0.5mg sublingual B/N was prescribed each twelve hours (N=1), or each evening (N=6) concurrent with other RLS medications. One subject discontinued B/N secondary to anxiety/insomnia.RLS symptoms and signs ( i.e., PLM) were promptly eliminated in two subjects. Dizziness/sleepiness/gait instability necessitated discontinuation or ongoing downwards dose titration. Four subjects (2 retirees) realized a profound, immediate benefit free of AEs for 2-6 months. IRLSSG rating scale severity decreased from 31.3 ± 6.7 to 4 ± 8 and insomnia severity index from 19.8 ± 6.1 to 1.3 ± 1.9. CPAP usage ≥ 4 hr/night increased from 39 to 68%, and 72 to 82%, and by 65 and 45 min/night, respectively, in two subjects). Employment (N=1) and premorbid work productivity (N=1) were regained. Conclusion: Sleep, CPAP adherence, and quality of life in chronic RLS patients experiencing augmentation, treatment refractoriness, or side effects with traditional opioids, can benefit from B/N. Incorporation into treatment algorithms warrants further investigation given B/Ns unique pharmacology and DEA schedule status. Support (If Any): Arthur L.Williams Jr.Foundation and grateful patients